2015
DOI: 10.1007/s00221-015-4251-7
|View full text |Cite
|
Sign up to set email alerts
|

Implicit guidance to stable performance in a rhythmic perceptual-motor skill

Abstract: Feedback information about error or reward is regarded essential to aid learners to acquire a perceptual-motor skill. Yet, simple error feedback does not suffice in guiding the learner towards the optimal solutions, when tasks have redundancy where the mapping between execution and performance outcome is unknown. The present study developed and tested a new means of implicitly guiding learners to acquire a perceptual-motor skill, rhythmically bouncing a ball on a racket. Due to its rhythmic nature, this task a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 86 publications
(112 reference statements)
0
14
0
Order By: Relevance
“…Such implicit guidance has potential advantages for learning in rehabilitation populations, because it allows for development of procedural skill that does not rely on working memory mechanisms [53, 54]. For example, returning to the virtual ball bouncing task earlier described, Huber et al [55] aimed to implicitly steer learners towards the desired solution of rhythmically bouncing the ball with dynamic stability. As mentioned, dynamic stability is desirable as it obviates the need for corrections, since they die out by themselves.…”
Section: Methodsmentioning
confidence: 99%
“…Such implicit guidance has potential advantages for learning in rehabilitation populations, because it allows for development of procedural skill that does not rely on working memory mechanisms [53, 54]. For example, returning to the virtual ball bouncing task earlier described, Huber et al [55] aimed to implicitly steer learners towards the desired solution of rhythmically bouncing the ball with dynamic stability. As mentioned, dynamic stability is desirable as it obviates the need for corrections, since they die out by themselves.…”
Section: Methodsmentioning
confidence: 99%
“…Such strategy could be used to train patients with weight-bearing asymmetries. Another example of this strategy is an experiment on visually guided ball bounding in a virtual ball bouncing task [36]. In this task, hitting the ball in the particular phase of the racket cycle leads to passively stable dynamics of the task (i.e., where the task can be performed without the perceptually-demanding racket corrections to the racket position).…”
Section: Uses Of Visual Information To Alter Sensorimotor Controlmentioning
confidence: 99%
“…In this task, hitting the ball in the particular phase of the racket cycle leads to passively stable dynamics of the task (i.e., where the task can be performed without the perceptually-demanding racket corrections to the racket position). Huber and Sternad delayed visual feedback of the racket which implicitly guided the performers to hit the ball in the passively stable regime, which led to a better performance on the task [36].…”
Section: Uses Of Visual Information To Alter Sensorimotor Controlmentioning
confidence: 99%
“…The existence of functionally equivalent motor solutions could explain how two people could arrive on different solutions yet with seemingly similar performance [2,9,50,51]. Previous work has shown that individuals could learn two non-adjacent motor solutions to a task and have difficulty finding the other solution unless it is explicitly demonstrated [44,45,52]. It is not clear how many such motor solutions may provide "good enough" solutions exist for a given task [53], and whether they can differ substantially in the muscle activation patterns.…”
mentioning
confidence: 99%